Preparation composite thin films of tin oxide with cobalt oxide and study their structure and optical characteristics - Ahmed K . Abass; Sura A. Abd Al-Hassan (Al-Qadisiyah Journal of Pure Science, 2019)
Both tin oxide, cobalt oxide and their composites thin films were deposited on a microscopic slid glass substrateat (400 ºC) utilizing chemical spray pyrolysis technique. The investigation the structural and optical characteristics of thin films were completed by many techniques such: Dispersive Spectroscopy (EDS), Energy X-Ray Diffraction (XRD), Field Emission- Scanning Electron Microscopy (FE-SEM), and Ultraviolet – Visible Spectroscopy (UV-Vis). The peaks of XRD show the crystallinebehavior of the films.The structure of SnO2 is tetragonal while the structure of Co3O4 is cubic. According to Scherrer equation in XRD analysis,all films which prepared to be nano materials. Thepresencesof securing oxygen, cobalt and tin segments with distinctive atomic and weight proportions for cobalt also tin were approved by EDS. FE-SEM images relate the homogenous films as thickly stuffed nano particles.. Optical band gaps of films are calculatedusingTauc plots, which are (4.5-2.5) eV.